PML in the Brain: From Development to Degeneration - Korb, Erica; Finkbeiner, Steve (Frontiers in Oncology, 2013)
The promyelocytic leukemia (PML) protein is the main component of PML nuclear bodies, which have many functions in a wide range of cell types. Until recently, PML was not known to have a function in the nervous system or even be expressed in the brain. However, recent reports have changed all of this. PML is found in neurons and functions in many aspects of the nervous system, including brain development, circadian rhythms, plasticity, and the response to proteins that cause neurodegenerative disorders. While the investigation of PML in the brain is still in its infancy, it promises to be a fascinating subject that will likely contribute to our understanding of the brain. Here we summarize what is known about PML expression and function in the brain and highlight both discrepancies in the field and areas that are particularly important to future research.